Dinamika Perilaku Penghuni Dalam Penggunaan Ruang Publik Dan Privat Pada Rusunawa Di Kota Mataram - Fachril Mayda Ashfari; Hartanto Budiyuwono (Jurnal Indonesia Sosial Teknologi, 2024)
In this research, the focus was given to two flats, namely Rusunawa Montong Are and Rusunawa Bintaro. This selection is based on significant differences in the physical environment, as well as the social status of the residents. So this is the basis for research on these two locations. This research aims to determine the behavior patterns of residents and the factors that influence residents' behavior in using public and private spaces in Rusunawa Montong Are and Rusunawa Bintaro. The research was conducted using qualitative research methods with an intrinsic case study approach. Then this research also uses behavioral mapping research techniques. The findings show that Rusunawa Montong Are and Rusunawa Bintaro are physically and socially different, but there are similar behavioral patterns of residents in the use of public and private spaces